(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
The risk of mudflow phenomena, as well as damages caused in Lori region have been estimated by scheme of mudflow classification according to the formula proposed by the UN (with some modifications). This is a step to forecasting mudflows.